Energy Security Versus the Pursuit of CO₂ Emission Reductions - Wierzbiński, Marcin (Bezpieczeństwo energetyczne a dążenie do redukcji emisji CO₂, 2010)
The author tries to answer the question if energy security is consistent with the pursuit of CO2 reduction. The problem is depicted from four perspectives, that is from international, national, regional and energy consumers’ perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 173-180
Keywords: energy security; CO2 emission reduction; climate change